Structural and magnetic characterization of MnxZn1-xFe2O4 (x=0.2; 0.35; 0.65; 0.8; 1.0) ferrites obtained by the citrate precursor method - Gimenes, R.; Baldissera, M. R.; da Silva, M. R. A.; da Silveira, C. A.; Soares, D. A. W.; Perazolli, Leining Antonio [UNESP]; da Silva, M. R.; Zaghete, M. A. [UNESP] (Elsevier B.V., 2012)
In this work the microstructure and magnetic properties of Mn-Zn ferrites powders were investigated. Mn(x)Zn1 - xTe2O4 powders where x = 0.2; 0.35; 0.5; 0.65; 0.8 and 1.0 were obtained by citrate precursor method. Citrate resin precursor was burned on air atmosphere at 400 degrees C for 3 h. Mn-Zn powders were calcined at 950 degrees C during 150 min under inert atmospheres: N-2 and rarefied atmosphere. Thermal analysis of precursor resin, phase evolution and microstructure of Mn-Zn ferrites powders were investigated by TG, DTA, XRD and SEM techniques. The powders calcined under rarefied atmosphere show spinet cubic structure and contamination of alpha-Fe2O3, while powders calcined under N-2 presents only the spinel cubic structure. Particle size was observed by SEM ranging from 80 to 150 nm. The magnetic properties were measured employing a vibrating sample magnetometer (VSM). It was observed that the saturation magnetization M-s increased with the increase of Mn content. The M-s of Mn0.8Zn0.2Fe2O4 calcined on rarefied atmosphere and Mn0.8Zn0.2Fe2O4 calcined on N-2 was 23.31 emu g(-1) and 56.23 emu g(-1), respectively. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Magnetic properties; Microstructure; Mn-Zn ferrite; Citrate precursor method